KORELASI PENGGUNAAN MEDIA AUDIO-VISUAL DAN PEMEROLEHAN KOSAKATA BAHASA INGGRIS DI TK GMIM BUKIT MORIA MALALAYANG - TAMBAYONG, SONYA FORTUNA; MARENTEK, ANDRIYANI; SENDUK, ARTER JODI (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2019)
ABSTRACT This research is an attempt to discover the correlation of English language acquisition and the audio-visual media usage on kindergarten students. The objectives of this research are to identify wheter the audio-viusal media usage can help the expansion of children English language acquisition and to analyze the factors that can affect the success and failure of the audio-visual usage in children English language acquisition. This study is based on the five principlas for creating effective second language learning environment from Erben, Ban and Castaneda (2009) and second language acquisition theory from Krashen (1985).The quailitative approach is applied in this study and the writer uses Random Sampling technique in choosing the participants. The data collection techniques were observation, documentation, interviews, Likert Scale as the field notes and quitionare. Pre-test and post-test also used to verify the original achievement from the participant and as the instrument to help analyzing the data. The result of this research shows that most participants had shown some progress in English language acquisition trough the audio-visual usage in number 54% on the pre-test and 86.25% on the post-test This research also discovered there are 4 positive factors and 5 negative factors which can affect the success of the audio-visual usage in children English language acquisition. Keywords: English language, Acquisition, Audio-Visual Media, Correlation, Children